Behavioral economics and climate protection: Better regulation and green nudges for more sustainability - Dominik Enste; Jennifer Potthoff (Institut der deutschen Wirtschaft (IW), 2021)
Protecting the climate is one of the greatest challenges our society is currently facing. In view of the heated political and social discussions surrounding this topic, the question naturally arises as to whether behavioral-economic insights can be used to sensitize German society to the dangers of climate change and to motivate it towards more sustainability. The field of behavioral economics provides empirical evidence of psychological factors that influence and even hinder sustainable behavior, ultimately leading to a gap between the will to act sustainably and actual behavior. Cognitive barriers, different social factors and group affiliations result in a complex system of diverse behavioral patterns, environmental attitudes, needs and expectations that must be considered when designing environmental policy instruments. People can be motivated to behave more ecologically without restricting their freedom of choice by the intelligent and effective use of green nudges rather than prohibitions. Identifying an effective, target-group-specific and ethical policy for counteracting climate change and encouraging more sustainable behavior requires an interdisciplinary approach combining behavioral-economic empiricism with ethical insights. – – Der Klimawandel zählt zu den größten Herausforderungen unserer Zeit. Angesichts der kontroversen politischen und gesellschaftlichen Diskussionen rund um Verbote oder höhere Umweltsteuern für mehr Klimaschutz stellt sich die Frage, inwiefern verhaltensökonomische Erkenntnisse genutzt werden können, um das Klima mit weniger drastischen Eingriffen in die Freiheit und die finanziellen Ressourcen der Menschen zu schützen. Die Verhaltensökonomik liefert empirische Belege für eine Vielzahl an psychologische Faktoren (Heuristiken und Biases), die (nachhaltiges) Verhalten beeinflussen. Moderne verhaltensökonomische Anreizsysteme nutzen diese Erkenntnisse rund um den Einfluss von Einstellungen, Bedürfnissen und Erwartungen sowie die soziologischen Milieuzugehörigkeiten bei der Gestaltung von umweltpolitischen Instrumenten. Mithilfe von intelligenten und effektiven Green Nudges kann durch zielgruppenspezifische und moralisch vertretbare Maßnahmen Nachhaltigkeit bei Verbrauchern effektiv und effizient erreicht werden: DefaultEinstellungen, soziale Vergleiche, Feedback-Prozesse oder Vereinfachungen richten sich differenziert an verschiedene Milieus, um den größtmöglichen Effekt zu erreichen.
Keywords: 330